2021
DOI: 10.3390/polym13183062
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dialkyl Peroxide Crosslinking on the Properties of LLDPE and UHMWPE

Abstract: Peroxide has been considered a chemical agent that can be used to tune the properties of polymeric materials. This research evaluated the influence of different concentrations of dialkyl peroxides on the mechanical, thermal, and morphological properties of linear low-density polyethylene (LLDPE) and ultra-high molecular weight polyethylene (UHMWPE). The neat polymer, as well as those with the addition of 1% and 2% by mass of dialkyl peroxides, were subjected to compression molding and immersion in water for 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The physical behavior (thermal stability, density, crystallization, and tensile properties) of crosslinked PE was also reported to change depending on the initial polymer molecular structure. [ 86 ] Liu et al [ 87 ] studied the effect of DCP content (0.3, 0.5, 1.0, 1.5, 2.0, and 2.5 wt%) on the properties of LDPE. It was found that increasing the DCP content led to higher crystallization temperature, degree of crystallization and elongation at break, while decreasing the tensile strength.…”
Section: Crosslinking Of Pementioning
confidence: 99%
“…The physical behavior (thermal stability, density, crystallization, and tensile properties) of crosslinked PE was also reported to change depending on the initial polymer molecular structure. [ 86 ] Liu et al [ 87 ] studied the effect of DCP content (0.3, 0.5, 1.0, 1.5, 2.0, and 2.5 wt%) on the properties of LDPE. It was found that increasing the DCP content led to higher crystallization temperature, degree of crystallization and elongation at break, while decreasing the tensile strength.…”
Section: Crosslinking Of Pementioning
confidence: 99%
“…Building desirable crystalline and amorphous hierarchal structures has an effect on the processing technology application of PE. Different approaches have been used to control the superstructures and hierarchical structures, govern the crystalline and amorphous regions of the PE matrix, which can confer high performance to the product 5–8 . Therefore, designing in situ experiments to observe the changes in PE crystals and amorphous structures is crucial for structural control and material application.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Furthermore, it increases the maximum operating temperature of PE because of the strong cross-linked network formation, making neat PE an ideal material for many applications, in particular cable and wire coating. 4,5 Currently, peroxide cross-linking is one of the widely used methods for PE cross-linking because of its ease of processing and lower cost investment, 6,7 and the use of organic peroxide as an initiator to generate free radicals during the cross-linking process. 8,9 An important limitation of PE is the poor flammability property that limits the scope of its application as a suitable material for fire protection.…”
Section: Introductionmentioning
confidence: 99%